1999
DOI: 10.1175/1520-0469(1999)056<3704:mrinhh>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Regimes in Northern Hemisphere Height Fields via MixtureModel Clustering*

Abstract: A mixture model is a flexible probability density estimation technique, consisting of a linear combination of k component densities. Such a model is applied to estimate clustering in Northern Hemisphere (NH) 700-mb geopotential height anomalies. A key feature of this approach is its ability to estimate a posterior probability distribution for k, the number of clusters, given the data and the model. The number of clusters that is most likely to fit the data is thus determined objectively. A dataset of 44 winter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
184
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(202 citation statements)
references
References 52 publications
18
184
0
Order By: Relevance
“…In both cases, the PDF is strongly skewed, as expected from the shape of the potential V (Fig. 6), thus defining two quasi-stationary states; mixture modeling (Smyth et al 1999) based on the jet position's time series confirms the assertion of two distinct, statistically significant Gaussian components (not shown). Both spectra have a red-noise character and roll off to a white spectrum for frequencies f < 1 year −1 .…”
Section: Atmospheric Component and Couplingmentioning
confidence: 99%
“…In both cases, the PDF is strongly skewed, as expected from the shape of the potential V (Fig. 6), thus defining two quasi-stationary states; mixture modeling (Smyth et al 1999) based on the jet position's time series confirms the assertion of two distinct, statistically significant Gaussian components (not shown). Both spectra have a red-noise character and roll off to a white spectrum for frequencies f < 1 year −1 .…”
Section: Atmospheric Component and Couplingmentioning
confidence: 99%
“…Whilst there have been attempts to explain atmospheric regimes through equilibrium solutions to low-dimensional atmospheric models (Charney and DeVore, 1979;Crommelin, 2003), the link to highdimensional atmospheric global circulation models and the actual atmosphere remains unclear. Regimes in such highdimensional systems are usually diagnosed from output data by examination of probability density function estimates for evidence of multimodality (Silverman, 1981;Corti et al, 1999;Ambaum, 2008;Woollings et al, 2010b) and applying statistical techniques such as clustering (Smyth et al, 1999;Hannachi, 2007;Cassou, 2008;Franzke et al, 2009), rather than by analysis of the dynamical equations themselves.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of these difficulties, agreement on at least a minimal set of weather regimes-extracted from daily, rather than monthly data-has emerged in the community (Cheng and Wallace 1993;Smyth et al 1999). A review of classification methods and results is included, for example, in Ghil and Robertson (2002) and Molteni (2002).…”
Section: Introductionmentioning
confidence: 99%
“…Using two distinct clustering procedures, these authors obtained four statistically significant weather regimes: the two phases of the North Atlantic Oscillation (NAO ϩ , NAO Ϫ ) and the two phases of a more hemispheric and zonally symmetric mode, which they identified with the Arctic Oscillation (AO ϩ ,A O Ϫ ). They found that these four regimes were in good agreement with previous results (Kimoto and Ghil 1993a,b;Michelangeli et al 1995;Corti et al 1997;Smyth et al 1999). By studying the Markov chain of transitions between regimes, they identified five highly significant transitions that could be organized into two cycles:…”
Section: Introductionmentioning
confidence: 99%